1649 Retrospective Analysis of Doxapram for the Treatment of Apnea of Prematurity. (October 2012) - Winter, J; Fekker, B; Gerhold-Ay, A; Kidszun, A; Schmidtmann, I; Whybra-Trümpler, C; Mildenberger, E
Abstract : Background and Aims: Only one small randomized controlled study on doxapram to treat apnea of prematurity is available. Before the implementation of a local treatment protocol, we aimed to evaluate the frequency of administration of doxapram in our NICU. We asked, if frequency and severity of apneas were affected by doxapram, if intubation for apnea was avoided, and if side effects occurred. Methods: We retrospectively analysed all premature infants < 30 weeks treated with doxapram during 03/2008 to 03/2010. We registered the number of apneas, bradycardias, and desaturations, an hour before, at the start of, and during 48 hours after onset of treatment. Results: 17 of 64 (27%) infants (mean gestational age 26.1 weeks, mean birth weight 733g) were treated during two years. All of them had been treated with caffeine before doxapram was applied. 70 therapy courses of 16 infants were analyzed. In 8 of 70 (11%) therapy courses, infants were intubated because of apnea during 48 hours of doxapram treatment. The frequency of apneas (2.24 vs. 0.17), bradycardias < 80/min (0.93 vs. 0.14), and desaturations < 80% (3.29 vs. 1.21) per hour decreased. No heart block occurred. However, restlessness was observed more frequently. Conclusions: Doxapram was applied to roughly a quarter of all very immature infants. Frequency and severity of apneas appeared to be reduced. Intubation because of apnea was avoided in a large proportion of infants. No severe side effects were recorded. More systematic studies on efficacy and safety of doxapram in premature infants are needed.